Effects of testosterone administration and feeding level on reproductive activity in sexually inactive goat bucks - DE SANTIAGO, A.; ALVARADO, J. F.; LÓPEZ, A. G.; TRUJILLO, G.; ÁLVAREZ, M. M.; MELLADO, M. (Journal of the Hellenic Veterinary Medical Society, 2018)
The aim of this study was to investigate the effect of the administration of testosterone to a well-fed or underfed sexually inactive goat bucks on their sexual behavior and semen characteristics. Twenty sexually experienced mixed-breed goat bucks (1.5 years of age) were randomly assigned to one of four treatments for a period of 71 days. Treatments consisted of diets with amount of nutrients to meet 1.0 times the nutrient maintenance requirements with the application of 25 mg testosterone every third day during 21 d (treatment 1T) or saline (treatment 1C). A third and fourth treatments received a diet 1/2 times the nutrient maintenance requirements with testosterone (1/2T) or saline (1/2C). Bucks on 1T and 1C had higher body weight, body condition score and scrotal circumference compared to 1/2T and 1/2C (P<0.05). Also, bucks on 1T and 1/2T had higher sexual odor compared to 1C and 1/2C (P<0.05). Mean serum testosterone concentrations were highest in 1T (4.78 ± 6.78 ng/ml) and lowest in 1/2C (0.56 ± 0.96 ng/ml; P<0.01). Semen volume, sperm concentration, and mass motility were not affected by treatments, but sperm progressive motility was lower (P<0.05) in 1/2C (46%) than the other treatments (52 to 57%). Courtship traits and mounts were more frequent (P<0.05) in 1T compared with the other treatments. Likewise, bucks in the 1T group had the shortest latency to first mount (82 seconds) compared to other treatments (110 to 164 seconds). These results indicate that testosterone administration to well-fed sexually inactive bucks provokes clearly defined sexual activity during the non-breeding season. However, these benefits are overridden by underfeeding goat bucks.